РЕАЛИЗАЦИЯ ТВОРЧЕСКИХ КОМПЕТЕНЦИЙ ДЛЯ УЛУЧШЕНИЯ ПРОФЕССИОНАЛЬНОЙ ПОДГОТОВКИ СПЕЦИАЛИСТА ТЕХНИЧЕСКОГО ПРОФИЛЯ - Мишенина, И.В.; Худоян, М.В.; Темираев, К.Б. (SCIENCE and SOCIETY, 2024)
The article talks about the implementation of creative competencies when restoring the professional training of technical specialists. The main stages of development of innovative specialists, the conditions for the formation of creative competencies in higher educational institutions, and issues of organizing the educational process were also covered.
Keywords: creative activity; formation of professional competencies; innovative economy; intellectual activity; self-development; creativity; competitive specialist